2007
DOI: 10.1128/jb.01692-06
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a Sugar Transporter Gene Cluster in a Hyperthermophilic Archaeon Using a Host-Marker System Based on Antibiotic Resistance

Abstract: We have developed a gene disruption system in the hyperthermophilic archaeon Thermococcus kodakaraensis using the antibiotic simvastatin and a fusion gene designed to overexpress the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase gene (hmg Tk ) with the glutamate dehydrogenase promoter. With this system, we disrupted the T. kodakaraensis amylopullulanase gene (apu Tk ) or a gene cluster which includes apu Tk and genes encoding components of a putative sugar transporter. Disruption plasmids were intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 67 publications
1
82
0
Order By: Relevance
“…S3 and S4). The maltodextrin ABC transporter system and amylopullulanase, both confirmed to play major roles in maltopolysaccharide assimilation (41), increased over 4-19-fold. In contrast, transcript levels of FBPase, which is essential for gluconeogenesis in T. kodakaraensis (32), were much higher under gluconeogenic conditions.…”
Section: Tk1769 Encodes a Protein Similar To Trmb-trmb Is An Archaealmentioning
confidence: 99%
“…S3 and S4). The maltodextrin ABC transporter system and amylopullulanase, both confirmed to play major roles in maltopolysaccharide assimilation (41), increased over 4-19-fold. In contrast, transcript levels of FBPase, which is essential for gluconeogenesis in T. kodakaraensis (32), were much higher under gluconeogenic conditions.…”
Section: Tk1769 Encodes a Protein Similar To Trmb-trmb Is An Archaealmentioning
confidence: 99%
“…One interesting example involved the in vivo disruption and analysis of a gene encoding reverse gyrase on the T. kodakaraensis genome, which revealed that the gene product functions in adaptation to high temperature, because reverse gyrase is highly conserved only in hyperthermophiles (Atomi et al, 2004). These efficient genetic tools have already been used to investigate several biological systems, such as the glycolysis pathway (Yoshida et al, 2006;Matsumi et al, 2007), natural product biosynthesis (Yokooji et al, 2009;Borges et al, 2010), transcription factors (Kanai et al, 2007(Kanai et al, , 2010, and operon transcription and translation machinery Hirata et al, 2008). However, these useful and powerful techniques have not yet been applied to the analysis of DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…In such a selection system, simvastatin, a competitive inhibitor of the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, was utilized to select for overexpression of the HMG-CoA reductase gene (hmgA) under the control of a strong constitutive promoter of glutamate dehydrogenase (Matsumi et al, 2007;Santangelo et al, 2008). This selection strategy has now been exploited in another hyperthermophilc euryarchaeon, Pyrococcus furious (optimal temperature 100 u C), with great success (Lipscomb et al, 2011;Waege et al, 2010).…”
Section: Introductionmentioning
confidence: 99%